Incorporating Learning Outcomes in Transfer Credit: The Way Forward for Campus Alberta? - Kennepohl, Dietmar (Canadian Journal of Higher Education, 2016)
Learning outcomes have become an integral part of the global trend in higher education reform and are employed in three interconnected areas: (1) quality assurance, (2) teaching and learning, and (3) transfer credit. The article touches briefly on the first two areas, but focuses discussion on employing learning outcomes in transfer credit. Using Alberta as a case study, its higher education system is examined and assessed, with emphasis on transfer credit, prior learning assessment, student mobility, and system coordination. Both the advantages and limitations of learning outcomes are presented, including balancing the needs of a wide variety of stakeholders. Taking lessons learned from similar international initiatives and an analysis of the Alberta context, the discussion culminates in a proposal for a way forward for this educational jurisdiction, promoting and incorporating learning outcomes as an important component of systematic and transparent method of transfer credit.